What is Universal Everything? - Brook, Tony; Shaughnessy, Adrian; Lee, Antonia; Pyke, Matt (London : Unit Editions Studio, 2019)
Matt Pyke, founder and creative director of Universal Everything, calls his studio a 'digital art and design collective'. And after 15 years of revolutionary work in the digital realm, UE has its first book, 'What is Universal Everything?' 'What is Universal Everything?' examines 24 of the studio's most exciting projects, from work for clients such as Microsoft, Hyundai and MTV, through to projects for Radiohead and the Science Museum in London. For each piece of work, Pyke collaborates with a pool of international creative talent from his base in Sheffield in the north of England. The book also focuses on several of UE's self-initiated projects that keep the studio pushing forward. These speculative explorations, says Pyke, are concerned with 'trying to invent the future before we get there'. The book also includes two essays and extensive interviews throughout, 90 pages of Pyke's hand-drawn sketches, as well as detailed listings of the studio's numerous sources of inspiration - from music to literature; from places to food.
Essays. Universal Everything : humanising the digital / by Adrian Shaughnessy -- A universal language of everything / by Antonia Lee -- Interview. Matt Pyke in conversation / with Adrian Shaughnessy -- Inspiration -- Sketches -- Work.
boek
Keywords: Pyke, Matt; Universal Everything (Firm)